Prevalence, age of onset, and natural history of thyroid disease in Pendred syndrome. Issue 8 (1st August 1999) - Reardon, William; Coffey, Rebecca; Chowdhury, Tanzina; Grossman, Ashley; Jan, Hikmat; Britton, Keith; Kendall-Taylor, Pat; Trembath, Richard
Abstract : BACKGROUND: We have sought to establish the prevalence of goitre within a Pendred syndrome (PS) cohort and to document the course of thyroid disease in this patient group. As part of a genetic study of PS we have assessed 57 subjects by perchlorate discharge test and in 52 (M 21, F 31, age range 9-54 years) a discharge of radioiodide of >10% was observed. RESULTS: Goitre was present in 43 (83%) of the cohort (28 F, 15 M), generally developing after the age of 10 years, 56% remained euthyroid (age range 9-37 years), and 19 patients (44%) had objective evidence of hypothyroidism, all of whom had goitre. CONCLUSIONS: In summary, thyroid dysfunction in PS is variable and inclusion of goitre as a diagnostic requirement will maintain significant underascertainment. The recent identification of the genetic defect underlying PS is likely to provide an important diagnostic aid in the identification of this disorder and this communication should assist clinicians in identifying deaf patients who ought to be considered for this investigation.